Quorum-sensing regulation in staphylococci—an overview - Le, Katherine Y.; Otto, Michael (Frontiers in Microbiology, 2015)
Staphylococci are frequent human commensals and some species can cause disease. Staphylococcus aureus in particular is a dangerous human pathogen. In staphylococci, the ability to sense the bacterial cell density, or quorum, and to respond with genetic adaptations is due to one main system, which is called accessory gene regulator (Agr). The extracellular signal of Agr is a post-translationally modified peptide containing a thiolactone structure. Under conditions of high cell density, Agr is responsible for the increased expression of many toxins and degradative exoenzymes, and decreased expression of several colonization factors. This regulation is important for the timing of virulence factor expression during infection and the development of acute disease, while low activity of Agr is associated with chronic staphylococcal infections, such as those involving biofilm formation. Accordingly, drugs inhibiting Agr are being evaluated for their capacity to control acute forms of S. aureus infection.